Adult Programs in the Library. - Lear, Brett W. (ALA Editions, 2002)
It has always been important for libraries to serve their communities with good programming. But as technology and bookstores pull customers away from traditional library services, programs have become a means to bringing people back into the library. Many libraries have even received national attention for increasing attendance with exceptional programming services. So, how are you going to develop top-notch programs to revitalize your library? The first in the new ALA Programming Guides series, Adult Programs in the Library will give you all of the need-to-know's. Program development and eve.